2013
DOI: 10.7314/apjcp.2013.14.11.6961
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Genotypes and Cervical Cancer in Northeast Thailand

Abstract: Human papillomavirus (HPV) is a major cause of cervical cancer. More than 100 HPV genotypes have been identified; however the distribution varies geographically and according to ethnicity. The purpose of this study was to investigate the prevalence and distribution of HPV subtypes among Northeast Thai women. Subjects included 198 cases of SCCA and 198 age-matched, healthy controls. HPV-DNA was amplified by PCR using the consensus primers GP5+/6+ system followed by reverse line blot hybridization genotyping. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…In low incidence area of cervical cancer in Songkhla HPV infection was found 3.8%, while in high incidence area in Lampang HPV infection was found 8.0%. Earlier studies of cervical and vulvar lesions in Thailand demonstrated HPV-16 to be most prevalent (Natphopsuk et al, 2013;Ngamkham et nal., 2013;Swangvaree et al, 2013;Siriaunkgul et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…In low incidence area of cervical cancer in Songkhla HPV infection was found 3.8%, while in high incidence area in Lampang HPV infection was found 8.0%. Earlier studies of cervical and vulvar lesions in Thailand demonstrated HPV-16 to be most prevalent (Natphopsuk et al, 2013;Ngamkham et nal., 2013;Swangvaree et al, 2013;Siriaunkgul et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The role of HPV as an etiologic factor of SCC in the other sites of anogenital tract has been increasingly recognized and genotype distribution has been assessed in cervical lesions in Thailand (Natphopsuk et al, 2013;Swangvaree et al, 2013). In vulvar carcinoma, the overall prevalence of HPV infection has been reported as 40.4%, which is lower than that of anal cancer in women (90.8%) and vaginal cancer (69.9%) (De Vuyst et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of HR-HPV infection among Thai women with ICC also has been consistently reported across the regions ranging from 77% to 97% (Tungsinmunkong et al, 2006;Siriaunkgul et al, 2008;Siriaunkgul et al, 2011;Chinchai et al, 2012;Natphopsuk et al, 2013;Siriaunkgul et al, 2013;Aromseree et al, 2014). In addition, more than 60% of ICC was HPV 16 and/or 18-related supporting that the majority of ICC in all regions is associated with HPV16 and/or 18.…”
Section: Invasive Cervical Cancer (Icc)mentioning
confidence: 81%
“…In addition, more than 60% of ICC was HPV 16 and/or 18-related supporting that the majority of ICC in all regions is associated with HPV16 and/or 18. Multiple HPV infection in Thai women varied widely from approximately 6% to 20% depending on histologic subtypes of ICC (Table 4) (Siriaunkgul et al, 2008;Siriaunkgul et al, 2011;Chinchai et al, 2012;Natphopsuk et al, 2013;Siriaunkgul et al, 2013).…”
Section: Invasive Cervical Cancer (Icc)mentioning
confidence: 99%